Factors of adult disabilities satisfaction towards motives of internet use in Malaysia - Haque, A. K. M. Ahasanul; Abdul Rahman, Rozailin; Hashim, Junaidah; Wok, Saodah (Zes Rokman Resources, 2018)
The level of satisfaction that one experiences while using the internet depends on type of disabilities. The internet offers an opportunity for inclusiveness – to view the global community of its users as one while recognizing its rich diversity. Internet technologies have the potential to give persons with disabilities the means to live on a more equitable basis within the global community in a manner that previously was not possible. This study aims to examine the level of satisfaction usage of the internet and to provide empirical evidences for policy formulation on digital inclusion among persons with disabilities. Stratified random sampling procedure is used for the quantitative research design. Total 805 adult disabilities data collected according to region: North, West, South, East Coast and East Malaysia. Among them only 593 respondents used Internet and answered all questions and considered for analysis. Finally this study needs to be conducted by using a bigger combination of independent variables with a more comprehensive model and the analysis need to further be expended and carried out using correlation and regression analysis to testify satisfaction effects on motives of Internet use.